Mendelian randomization study reveals a causal relationship between serum iron status and coronary heart disease and related cardiovascular diseases - Liu, Fenglan; Liu, Yanfei; Xu, Shihan; Wang, Qing; Xu, Fengqin; Liu, Yue (Frontiers in Cardiovascular Medicine, 2023)
Background Growing observational studies have shown that abnormal systemic iron status is associated with Coronary heart disease (CHD). However, these results from observational studies was not entirely consistent.It remains unclear whether this relationship represents causality.It is necessary to explore the causal relationship between iron status and CHD and related cardiovascular diseases (CVD). Objective We aimed to investigate the potential casual relationship between serum iron status and CHD and related CVD using a two-sample Mendelian randomization (MR) approach. Methods Genetic statistics for single nucleotide polymorphisms (SNPs) between four iron status parameters were identified in a large-scale genome-wide association study (GWAS) conducted by the Iron Status Genetics organization. Three independent single nucleotide polymorphisms (SNPs) (rs1800562, rs1799945, and rs855791) aligned with four iron status biomarkers were used as instrumental variables. CHD and related CVD genetic statistics We used publicly available summary-level GWAS data. Five different MR methods random effects inverse variance weighting (IVW), MR Egger, weighted median, weighted mode, and Wald ratio were used to explore the causal relationship between serum iron status and CHD and related CVD. Results In the MR analysis, we found that the causal effect of serum iron (OR = 0.995, 95% CI = 0.992–0.998, p = 0.002) was negatively associated with the odds of coronary atherosclerosis (AS). Transferrin saturation (TS) (OR = 0.885, 95% CI = 0.797–0.982, p = 0.02) was negatively associated with the odds of Myocardial infarction (MI). Conclusion This MR analysis provides evidence for a causal relationship between whole-body iron status and CHD development. Our study suggests that a high iron status may be associated with a reduced risk of developing CHD.